Muslim fashion: challenging transregional connectivities between Malaysia and the Arabian Peninsula - Thimm, Viola (TRaNS, 2021)
In Malaysia, a Muslim-majority country in Southeast Asia, a dynamic market for Muslim fashion has evolved over the past decade, especially concerning the abaya, a female Muslim dress. Malay Malaysian designers, producers and consumers focus on this garment because it represents a style of female Islamic clothing that is perceived as ‘authentic’. The abaya originates from the Arabian Peninsula and is generally worn by Arabic Muslim women with a syariah-compliant design that is commonly simple, loose and opaque. Embedded into the broader marketising processes of a halal industry in Malaysia, Malay women started to adopt this material object and transformed it into a distinct expression of Malaysian Muslim style. The original abaya that follows Islamic rules became a colourful and decorated dress. This transformative process is not only an expression of variation in fashion and style but profoundly transcends powerful social, placial and spatial orders within the Muslim world. The Malaysian fashion market for abayas is embedded in wider dynamics of sacred landscaping in which the Arabian Peninsula is considered to be the ‘centre of Islam’ while Malaysia is positioned and positions itself at the margins. However, Malay Malaysian social actors have shifted this constellation towards a Malaysia that has pushed itself to the forefront of a commercialising Islam through the development of the related Muslim fashion market, among other things. Thus, within a Muslim world order, transregional connections lead to an entangled web of meaning-making regarding power structures, Islamic principles and social practices.
Gesehen am 20.06.2024